Enablers for IBC: integral cell and module development and implementation in PV industry. (September 2017) - Cesar, Ilkay; Guillevin, Nicolas; Mewe, Agnes A.; Spinelli, Pierpaolo; Burgers, Antonius R.; Rosca, Victor; Okel, Lars A.G.; Geerligs, Bart J.; Weeber, Arthur W.; Sawallich, Simon; Nagel, Michael
Abstract: An integral solar cell and module concept is developed based on an IBC cell design with a front floating emitter (FFE). The FFE renders the cell resilient to electrical shading and reduces the demands on feature size. The cells are bi-facial by design. We interconnected 6" IBC cells using a conductive back sheet foil, resulting in a visually appealing mono-facial solar module. The IBC cells are made using a process close to existing industrial n-PERT processing, their production in an industrial pilot line has been demonstrated. The cells can be produced at the cost level of a PERC cell. The paper shows how the current cell efficiency of 21.1% cell will be increased beyond 22% in 2017 and what enablers are required to industrialize this concept. One such enabler we report on is high resolution Rsheet mapping using near-field THz scanning.